Therapeutic equivalence of generic imipenem/cilastatin for therapy of infections at Siriraj Hospital - Sukij Piyasirisilp (2018)
cilastatin (YungjinR) has been available in Siriraj Hospital since 2007. Since imipenem/cilastatin is usually given to the patients with serious hospital-acquired infections, the generic imipenem/cilastatin must be therapeutically equivalent to the original imipenem/cilastatin. The objective of the study was to compare effectiveness and safety of generic imipenem/cilastatin with original imipenem/cilastatin for therapy of infections in hospitalized patients at Siriraj Hospital. Material and Method: Medical records of adult hospitalized patients at Siriraj Hospital who received imipenem/cilastatin at least 48 hours during June 2007 to September 2008 were reviewed. The effectiveness data of 300 patients who received original imipenem/cilastatin were compared with those of 300 patients who received generic imipenem/cilastatin in order to determine if a difference in composite favorable outcome of both formulations was within 10%. Results: The demographics, clinical features of infections, site of infections, type of causative organisms and concomitant antibiotics of the patients in both groups were not significantly different. The overall favorable outcomes in the original imipenem/cilastatin and the generic imipenem/cilastatin groups were 65% and 58.7% respectively (absolute difference 6.3%, 95% CI -1.4% to 14%). Cure rates of infections in the original imipenem/cilastatin and the generic imipenem/cilastatin groups were 35% and 28.7% respectively (absolute difference 6.3%, 95% CI -1.1% to 13.7%). Super-infection rates in the original imipenem/cilastatin and the generic imipenem/cilastatin groups were 4.7% and 9% respectively (absolute difference -4.3%, 95% CI -8.5% to 0.3%). Mortality due to infections in the original imipenem/cilastatin and the generic imipenem/ cilastatin groups were 18.3% and 21.3% respectively (absolute difference -3%, 95% CI -9.4% to 3.4%). Overall mortality in the original imipenem/cilastatin and the generic imipenem/cilastatin groups were 35.3% and 43% respectively (absolute difference -7.7%, 95% CI -15.3% to 0.1%). The occurrence of adverse events in the patients in both groups was not significantly different. Conclusion: Although the point estimate of composite favorable outcome of the patients who received generic imipenem/ cilastatin (YungjinR) was < 10% of those who received original imipenem/cilastatin (TienamR), generic imipenem/cilastatin showed a trend for therapeutic non-equivalence to original imipenem/cilastatin because the upper limits of 95% confidence interval of differences of several important clinical outcomes were more than 10%.